Prevalence and aeroallergen sensitization in pediatric Allergic Rhinitis: A population-based study in Jeju, Korea - Min-su Oh; Miok Kim; Jung-Kook Song; Seong-Chul Hong (PLoS ONE, 2025)
Allergic rhinitis (AR) is a prevalent chronic disease among children, influenced by environmental and genetic factors. Understanding regional aeroallergen sensitization patterns is essential for targeted intervention. This study investigates the prevalence of AR and its associated aeroallergen sensitization among schoolchildren in Jeju, Korea. A cross-sectional, population-based study was conducted in 2016 on 1,067 schoolchildren aged 9–16 years. Data were collected using the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire and skin prick tests for 18 common aeroallergens. Statistical analysis was performed using multiple logistic regression to determine risk factors for AR. The prevalence of AR was 29.0%, with the highest sensitization rates observed for Dermatophagoides pteronyssinus (76.5%), Dermatophagoides farinae (60.9%), and Japanese cedar pollen (39.1%). Sensitization to multiple aeroallergens (polysensitivity) was significantly associated with increased AR risk (OR 1.58, 95% CI: 1.017–2.455, p = 0.042). Age-related variations in sensitization patterns were noted, with younger children showing higher overall sensitization rates. This study provides evidence of region-specific allergen sensitization patterns in pediatric AR. The high prevalence of Japanese cedar pollen sensitization highlights the need for further investigation into environmental exposure and potential preventive measures.